RANCANG BANGUN APLIKASI PENGHITUNGAN INVERS MATRIKS ORDO 3X3 DAN 4X4 DENGAN METODE INCREMENTAL PROCESS BERBASIS MULTIMEDIA: Sofida Kartika Ningrum, Efy Yosrita - Jurnal, Redaksi Tim (PETIR, 2018)
Matrix inverse method consists of a method of partitioning a matrix, adjoint matrix, and elementary row operations. In the matrix inverse learning application that was created earlier, it was contains only one method of inverse matrix in each application. Existing application still separated for each method cause made by different people. When lecture used the application in courses of Linear Algebra, actualy the application can only run on a particular computer device. This was motivated writers to created applications that can run on all devices komputer and combines of all methods in a single application. Application form is accompanied by material simulations, exercises and games to enable students to understand the material of the inverse matrix given in class. Software development methods or SDCL (System Development Life Cycle) is the method Incremental Process Model, interface design and coding using Microsoft Visual Studio 2010 Ultimate.